The level of psychological resilience of a student in conditions of distance learning - Vizniuk, Inessa Mykolaivna; Polishchuk, Anna Serhiivna (Insight: the psychological dimensions of society, 2020)
The purpose of the article is to determine features of psychological resilience of students during distance learning by indicators of their success. Methods: analysis, synthesis, systematization, generalization, comparison, specification and psychodiagnostic techniques. The results of the research empirically established the relationship between the level of psychological resilience formation and psychosomatic health in the research of the control group and similar indicators in the study of the experimental group. Experimental data show a significantly higher adaptability of the control group and their rational approach to life in conditions of distance learning, which is fundamentally important in preventive work to ensure the psychological health of the population of Ukraine. Emphasis is placed on activating the development of personal and value attitudes of students to psychosomatic health. A person’s psychosomatic health includes: his/her environment, behavior, thinking, beliefs, identity and spirituality. Based on these features, we have created reflexive mechanisms to activate the development of personal and value attitudes of students to psychosomatic health. It is noted that its essence is: to create an emotional and communicative background to support the safe life of the individual; in the formation of appropriate habits and thinking strategies that add ingenuity in the process of overcoming stress, managing the consistency of a healthy lifestyle, adequate behavior. The conclusions show that in the educational process, the reference control (traditional form of learning) and experimental (with elements of distance learning) groups, according to the error of performance indicators do not have a significant difference, and therefore we can assume that performance indicators are approximately the same as for distance learning.